Determination of isoscoparin in mouse blood using UPLC–MS/MS and its pharmacokinetics. (6th June 2022) - Huang, Xueli; Jiang, Haodong; Liang, Qishun; Ma, Yizhe; Wang, Xianqin
Abstract: This study developed a UPLC–MS/MS method to detect isoscoparin in mouse blood, determined the pharmacokinetics of isoscoparin in mice after intravenous (5 mg/kg) and intragastric (20 mg/kg) administration, and calculated the absolute bioavailability. A HSS T3 column was used for separation, and the column temperature was set at 40°C. The mobile phases were acetonitrile and 0.1% formic acid, and the gradient elution procedure was used. The blood sample was treated with protein precipitant with acetonitrile–methanol (9:1, v/v). Multiple reaction monitoring mode was used for quantitative analysis in electrospray positive‐ion mode. It showed a good linear relationship in the range of 1–4000 ng/mL ( r > 0.998); the intra‐day and inter‐day precision was <12%, and the accuracy was 86–112%. The recovery was >68%, and the matrix effect was 86–90%. The half‐life of isoscoparin was relatively short in mice, and the bioavailability was 2.6%. The developed UPLC–MS/MS method was rapid, sensitive, and suitable for the pharmacokinetics of isoscoparin in mice.